Cloud Point Extraction as a Method for Preconcentration of Metal Ions - Nusreta Hasic; Emir Horozic (Journal of Engineering & Processing Management, 2020)
Cloud point extraction (CPE) is an attractive technique that reduces solvent con- sumption and exposure, disposal costs, and process time. This method has an im- portant practical application and is used to separate and concentrate the analyte as a step before its determination, and after the formation of a poorly water-soluble complex. Use of nonionic surfactants as ”green solvents” which represent an effec- tive alternative to toxic organic solvents (in classical extraction), along with other advantages, such as low cost and low flammability, makes this method attractive and worth further research and optimization. This paper presents a detailed de- scription of the principles, procedure, advantages, disadvantages and application of CPE.
Keywords: Cloud point; surfactant-rich phase; nonionic surfactants; metal extraction; ”green” method